2021
DOI: 10.3389/fpls.2021.674433
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Nitrogen Deficiency on Wheat (Triticum aestivum L.) Grain During the Medium Filling Stage: Transcriptomic and Metabolomic Comparisons

Abstract: Nitrogen (N) supplementation is essential to the yield and quality of bread wheat (Triticum aestivum L.). The impact of N-deficiency on wheat at the seedling stage has been previously reported, but the impact of distinct N regimes applied at the seedling stage with continuous application on filling and maturing wheat grains is lesser known, despite the filling stage being critical for final grain yield and flour quality. Here, we compared phenotype characteristics such as grain yield, grain protein and sugar q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 107 publications
(138 reference statements)
1
17
0
Order By: Relevance
“…Heerah et al [ 53 ] revealed that WRKY1 regulates the expression of various nitrogen-related genes, including NRT2.1 and AMT1.1 genes, in Arabidopsis. Wang et al [ 54 ] reported that the expression of TIFY10c was promoted under N deficiency in wheat. Similarly, overexpression of TabHLH1 enhances the expression of NRT2.2 and several genes involved in the antioxidant enzyme under low-N stress in wheat [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heerah et al [ 53 ] revealed that WRKY1 regulates the expression of various nitrogen-related genes, including NRT2.1 and AMT1.1 genes, in Arabidopsis. Wang et al [ 54 ] reported that the expression of TIFY10c was promoted under N deficiency in wheat. Similarly, overexpression of TabHLH1 enhances the expression of NRT2.2 and several genes involved in the antioxidant enzyme under low-N stress in wheat [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A series of physiological and molecular mechanisms underlying crop adaptation to N deficiency have been demonstrated, such as coordinating carbon (C) and N metabolisms, regulating root architecture, modulating phytohormone signaling, enhancing N uptake and translocation, and accumulating stress tolerance-related compounds [ 8 , 20 , 21 , 22 , 23 , 24 ]. Since total N content and crop growth are affected by N limitation, metabolome analysis has been performed to identify N deficiency responsive metabolites and metabolic pathways, dissecting the adaptive mechanisms through regulation of metabolic profiles in many crops, such as rice ( Oryza sativa ), maize ( Zea mays ), wheat ( Triticum aestivum ), barley ( Hordeum vulgare ), soybean ( Glycine max ), tomato ( Solanum lycopersicum ), and rapeseed ( Brassica napus ) [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. A summary of metabolome analyses of crops responses to N deficiency is presented in Table 1 .…”
Section: Metabolisms Responsive To Nutrient Deficiencies In Cropsmentioning
confidence: 99%
“… [ 36 ] Wheat ( Triticum aestivum ) Grains 25 days post anthesis GC–MS 77 Increasing ornithine, cysteine, aspartate, and tyrosine; promoting sugar accumulation. [ 31 ] Rapeseed ( Brassica napus ) Leaves 14 LC–ESI-MS/MS 175 Decreasing aspartic acid; increasing l -alanine. [ 32 ] Rapeseed ( Brassica napus ) Roots 14 LC–ESI-MS/MS 166 Increasing aspartic acid.…”
Section: Metabolisms Responsive To Nutrient Deficiencies In Cropsmentioning
confidence: 99%
“…An efficient use of N fertilisation that meets sustainability is necessary since it is the nutrient that most affects crop production and quality, but it is costly and its excessive use can cause soil and water pollution (Vicente et al, 2019b;Wang et al, 2021). Then, it is important to identify those physiological and metabolic parameters affected by N with an impact on GY and GQ.…”
Section: N Fertilisation Has a Significant Effect On Grain Yield And ...mentioning
confidence: 99%
“…N metabolism is a key factor for plant growth, with a crucial impact on GY and GQ traits, such as protein content, dough quality, and processing characteristics (Zörb et al, 2018;Wang et al, 2021). It is relevant for the wheat research to understand the N assimilation and remobilisation taking place in the different green organs, especially during grain filling.…”
Section: Introductionmentioning
confidence: 99%